Penerapan Hukum Lingkungan dalam Menghadapi Krisis Perubahan Iklim Global - Muhammad Defa Hakim; Mohammad Hayqal Rafi Khamid; Ubaidillah Kamal (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstrak. The global climate change crisis is the main challenge faced by the world today. Its broad impact on the environment and humans requires a serious response from various sectors, including environmental law. The Indonesian government has actively participated in various international forums, such as the Climate Change Convention, Kyoto Protocol, Paris Agreement, and Bali Roadmap, together with UN member countries in their commitment to tackle global warming. In Indonesia, efforts to control the climate crisis are carried out through adaptation and mitigation strategies. Adaptation efforts are focused on areas that are vulnerable to climate change, including water resources, agriculture, fisheries, coastal and marine areas, infrastructure and settlements, health and forestry. Meanwhile, mitigation efforts include steps such as saving electricity and water use, implementing the 5R concept (Rethink, Reduce, Reuse, Recycle, Replace), maximizing the use of renewable energy, using environmentally friendly equipment, increasing greening activities, increasing the efficiency of vehicle use, and encouraging local communities to participate in environmentally friendly practices. Keyword : Global Climate, Government Regulation, National Action Abstrak. Krisis perubahan iklim Global merupakan tantangan utama yang dihadapi oleh dunia saat ini. Dampaknya yang luas terhadap lingkungan dan manusia memerlukan respons serius dari berbagai sektor, termasuk hukum lingkungan. Pemerintah Indonesia telah berpartisipasi aktif dalam berbagai forum internasional, seperti Konvensi Perubahan Iklim, Protokol Kyoto, Paris Agreement, dan Bali Roadmap, bersama negara-negara anggota PBB dalam komitmen untuk mengatasi pemanasan global. Di Indonesia, upaya pengendalian krisis iklim dilakukan melalui strategi adaptasi dan mitigasi. Upaya adaptasi difokuskan pada area yang rentan terhadap perubahan iklim, termasuk sumber daya air, pertanian, perikanan, pesisir dan laut, infrastruktur dan pemukiman, kesehatan, dan kehutanan. Sedangkan upaya mitigasi mencakup langkah-langkah seperti penghematan penggunaan listrik dan air, menerapkan konsep 5R (Rethink, Reduce, Reuse, Recycle, Replace), maksimalisasi penggunaan energi terbarukan, penggunaan peralatan ramah lingkungan, peningkatan kegiatan penghijauan, serta efisiensi penggunaan kendaraan, dan mengajak masyarakat sekitar untuk berpartisipasi dalam praktik ramah lingkungan. Kata kunci : Iklim Global, Peraturan Pemerintahan, Aksi Nasional